Alien neighbours: foreigners in contemporary Shanghai - De Giorgi, Laura (Journal of Architecture and Urbanism, 2017)
One distinctive facet of Shanghai’s cosmopolitanism and openness to the outer world is the foreign presence in the city. Partially reviving the myth of the old pre-1949 Shanghai, in the last twenty years Shanghai has become again a pole of attraction for foreign migrants, and it actually hosts one of the most numerous community of residents of alien nationality in the People’s Republic of China. Drawing from sociological and ethnological literature, from official reports and media coverage of the topic, this paper overviews the impact of foreign communities in Shanghai and investigates how Shanghai local migration policies and media discourse shape the meaning of this phenomenon with respect to the definition of Shanghai’s identity as a globalizing and a Chinese metropolis as well.